Feature-guided convolution for salient rendering of 3D meshes. (4th December 2014) - Min, Kyungha
We present a novel algorithm that depicts the salient shape of a 3D mesh by mimicking pencil drawing style. In estimating the saliency of a mesh, we consider both view-independent and view-dependent saliency. The view-independent saliency is estimated from the strength of silhouette and the view-dependent one is computed by approximating the curvature of a mesh. We extend the pencil drawing algorithm for a mesh and develop a convolution-based scheme that renders the saliency of a mesh in a pencil drawing style. Furthermore, we develop a scheme that controls the coherence of the depiction through an animation of a mesh.